Rancang Bangun Sistem Pengajuan Kerjasama Pemasaran Berbasis Website - Harfizar, Harfizar; Soip, Dede; Gerardo, Danield (UNIVERSITAS RAHARJA, 2023)
PT Generasi Prima Solusi is a company engaged in services and services that has collaborated with several construction company partners and BUMN in terms of services to meet the needs of marketing services and business consulting. The process of information and submission of cooperation from PT Generasi Prima Solusi is still very manual by coming directly to companies or contacting companies to offer services so that they are not right on target. Therefore, PT Generasi Prima Solusi urgently needs a web-based computerized system to provide convenience in accessing data easily, safely, and accurately so that it can overcome all difficulties and errors that occur. By using the SWOT analysis method, it is possible to identify weaknesses in the system that is made so that the system can function properly. With this system, it is hoped that it can help and facilitate companies in submitting cooperation.